Natural resources of Trinidad and Tobago - Cooper, St G.C., ed. (Edward Arnold LondonGB, 1981)
Contains articles on physical resources focusing inter alia, on soils, water, minerals and energy from petroleum and non-conventional resources. Section two discusses biological resources with articles on forests, aquatic resources, and food and agriculture. Section three deals exclusively with human resources.